A Review of the Technological Advancements in Detecting Lung Cancer Severity Among the Malaysian Population - Muhammad Zaim Kashfi Zaman; Sofina Tamam (Academy of Sciences Malaysia, 2026)
Tier 2- Indexed by SCOPUS/MyCite